Starchy Crops Morphology, Extraction, Properties and Applications: Vol 1: Underground Starchy Crops of South American Origin: Production, Processing, Utilization and Economic Perspectives - Cereda, Marney Pascoli [UNESP]; Vilpoux, Olivier François (Elsevier, 2022)
Starchy Crops Morphology, Extraction, Properties and Applications is the first volume of the Underground Starchy Crops of South American Origin book series. Organized in five volumes, this series brings information on the applied level of producing and using starch from a range of plants grown in tropical and subtropical areas that have South American origin. This book presents the characteristics and properties of starches for raw materials grown in tropical climates. It allows comparing starches from 3 types of storage organs, roots, tubers and rhizomes, with different morphological structures and physiology. It contains the methodologies of extraction and analysis, describing the commercial process with the commercial equipment’s and its by-products and wastes. It also includes topics on fraud detection, nutritional aspects, and starch structure. Edited by a team of experts with solid background on starch extraction research, the books are aimed at all those involved in research and development as well as quality control and legislation in the field of starch.